Governing global telecoupling toward environmental sustainability - Jens Newig (Resilience Alliance, 2020)
Telecoupling constitutes a particular class of globalized environmental issues that are neither local-cumulative, nor transboundary, nor concerning global commons, but that arise because of specific linkages between distal regions. Such telecoupled issues, e.g., associated with global commodity chains, waste flows, or migration patterns, have been receiving increasing attention from scholars of global land change science. Although governance research has mostly studied existing institutional responses to these issues, telecoupling opens up a problem-oriented perspective on issues of environmental sustainability that occur regionally, but that arise because of global linkages, and raises novel questions about how such issues are and could be governed in a global architecture. We draw insights from existing literature on globally interconnected phenomena to advance our understanding of governing telecoupling toward environmental sustainability. We first identify and discuss five particular challenges that telecoupling poses to global environmental governance: knowledge deficits, divergent interests, high transaction costs of cooperation, the weak legitimacy base of current governance arrangements, and policy incoherence and fragmentation. Second, we review conceptual literature that meaningfully address the governance of telecoupling, while utilizing differing terminologies, for example, through reference to "flows," "chains," or "multiscalar" issues. Building on this, we elaborate on how currently debated governance approaches respond to the identified challenges. We conclude with a brief note on where we believe the discussion on governance of telecoupling stands, and where we see directions for future research.